Levothyroxine Replacement Improves Oxidative Status in Primary Hypothyroidism - Masullo, Laís Farias; Magalhães, Rejane Araújo; Lemes, Romélia Pinheiro Gonçalves; de Almeida Filho, Tarcísio Paulo; de Castro, Marilena Facundo; Maia Filho, Pedro Aurio; Cunha, Tainá Osterno Vasconcelos; Quidute, Ana Rosa Pinto; Fontenele, Eveline Gadelha Pereira; Sun, Guang; Martins, Manoel Ricardo Alves (Frontiers in Endocrinology, 2018)
Objective: Although hypothyroidism has been linked to oxidative stress, data regarding the relationship between thyroid hormone levels and oxidative stress is still inconsistent. This study was designed to evaluate the effect of levothyroxine replacement on oxidative stress in women with primary hypothyroidism. Design: a total of 25 female patients with primary hypothyroidism were included. Oxidative stress markers were measured before and after levothyroxine replacement treatment in all patients. Methods: Oxidative stress was evaluated through the measurement of oxidants (thiobarbituric acid reactive substances [TBARS] and nitrite/nitrate levels), and antioxidants (superoxide dismutase and catalase activity). Results: Antioxidant catalase activity (63.77 ± 23.8 vs. 50.12 ±12.75 atv/min; p = 0.03) was significantly increased and the levels of TBARS (3.02 ± 0.86 vs. 3.55 ± 0.87 µM; p=0.03) were significantly decreased in the state of euthyroidism after levothyroxine replacement compared to the hypothyroidism before levothyroxine treatment. No significant change in neither nitrite/nitrate concentration (p = 0.18) nor in superoxide dismutase activity (p = 0.93) after L-T4 adjustment was found. Conclusions: Our data demonstrate that levothyroxine replacement improved oxidative status in patients with primary hypothyroidism, indexed by the significantly decreased levels of malonaldehyde (MDA) and increased catalase (CAT) activity.